Asymmetric spread of heart rate variability. (July 2020) - Rohila, Ashish; Sharma, Ambalika
Highlights: A novel asymmetry index is proposed. The study of effect of meditation on HRA is performed. A comparative analysis of HRA in synthetic HRV signals and real HRV signals is performed. A comparative analysis of the performance of different HRA indices is presented. Abstract: Objective: The variability related to acceleration and deceleration of heart rate contributes unevenly to the overall heart rate variability (HRV). Thus, the spread of heart rate is asymmetric. Despite developing several heart rate asymmetry (HRA) measures, none examines this disparity in HRV. Therefore, a new HRA measure, asymmetric spread index (ASI), is proposed to measure asymmetry in the variability of heart rate associated with acceleration and deceleration. HRA generally arises due to cardiac autonomic modulation. However, the exact underlying phenomenon is unknown. Therefore, the study of HRA is performed in cardiac pathologies, synthetic HRV signals, and meditation. Methods: Like other HRA measures, ASI is defined by using the Poincaré plot. The surrogate data analysis was performed to examine that ASI represents a physiological phenomenon and not an artifact of the method. Statistical analysis and receiver operating characteristic analysis were performed for evaluating the performance of HRA indices. Results: HRA is found increased in patients with heart failure and arrhythmia. Synthetic HRV signals show less asymmetry than real HRV signals. The HRA increases during meditation. Experimental results indicate that variability shifts from the acceleration part to the deceleration part during meditation, and vice versa. Conclusion: The ASI quantifies the uneven spread of heart rate that would remain unexplored with existing asymmetric measures. It shows better discriminating power than existing HRA. Significance: Since HRA is a new area, further studies are required to establish its clinical significance. The ASI may help in understanding the underlying mechanism of HRA.